Hakam/tahkim in resolving family disputes: the practice in the Syariah Court of Malaysia and Singapore - Abdul Hak, Nora (2006)
This seminar will focus on the provisions and the practice of alternative dispute resolution (ADR) in family disputes, with special reference to the resolution of disputes by means of hakam. Resolving disputes by hakam is recognized and encouraged in Islam as a means of dispute resolution, not only in family disputes but also in other disputes such as commercial, construction and international disputes. Provisions for family dispute resolution have been included in the Islamic Family Law Act of Malaysia and the Administration of Muslim Law Act of Singapore. Although the two Acts are similar in principle, the practice in Malaysia is beset with problems, while the practice in Singapore seems much more positive. The provisions of the two Acts will be discussed and compared, and suggestions and recommendations to further improve the current provisions and practice will be made.